(untitled) - Glenn, Walter J. (San Francisco, 2001)
Here’s the book you need to prepare for Exam 70-224, Installing, Configuring, and Administering Microsoft Exchange 2000 Server: Full coverage of every exam objective—all the information you need to know; Practical information on installing, configuring, and administering Exchange 2000 Server; Hundreds of challenging review questions, in the book and on the CD; Leading-edge exam preparation software, including a testing engine, simulation software, and electronic flashcards
Keywords: Electronic data processing personnel,Microsoft software,Client/server computing,Xử lý dữ liệu cá nhân; Certification,Examinations,Examinations